User-generated content vs. firm-generated content: do consumers trust fellow consumers more than firms? Evidence from the Saudi telecommunication sector - Ghaith Al-Abdallah; Len Tiu Wright (Cogent Business & Management)
The purpose of this research is to assess, examine, and compare the effects of user-generated content (UGC) and firm-generated content (FGC) on consumer buying behaviour for telecommunications products and services. A descriptive quantitative methodology was applied to attain this purpose. The targeted population for this research includes all telecommunications users in Saudi Arabia. The main data were derived from 1206 online surveys from a quota sample of consumers who recently acquired telecommunications services and have active social media profiles. SPSS version 23 was utilized to test the hypotheses. Among the UGC dimensions, both content valence and information richness have a statistically significant positive impact on the consumer buying process (CBP). While all FGC dimensions have a significant positive impact on the CBP, valence has the biggest impact, followed by trustworthiness, and then information richness. FGC influences CBP for telecommunications products and services more than UGC. This paper bridges the literature gap about the comparative effect of UGC and FGC for these kinds of products and services, and the adopted methodology and large obtained sample provide statistically supported evidence for the study’s main results. This contributes to the broader discourse on content marketing and consumer trust by refining the conditions under which UGC or FGC is more influential, this research highlights that industry-specific factors play a critical role in shaping content credibility perceptions. Discussion and future research orientation are provided.